Grodno school of sociology of medicine: scientific field of research - Surmach, Marina Yu. (Journal of the Belarusian State University. Sociology, 2023)
The article briefly outlines the history of the formation of the sociology of medicine as a scientific specialty in Belarus, the content of the specialty is presented and its specificity in Belarus is shown. The article considers the role of the Grodno State Medical University, scientific cooperation with the professional community of Russian sociologists. The main milestones in the formation of the scientific school of sociology of medicine in Belarus are revealed, the directions of research currently being carried out by the young Grodno school of sociology of medicine, the spheres of practical application of research results are outlined.
Keywords: sociology of medicine; history of the formation of a scientific school; Grodno State Medical University; scientific specialty; research directions